Observational results for five short-period and five long-period comets. (January 2020) - Garcia, R.S.; Gil-Hutton, R.; García-Migani, E.
Abstract: In this work we studied the activity of a group of long and short period comets at different heliocentric distances in order to explore and compare their dust production and characteristics. The targets observed were the comets 22P/Kopff, 29P/Schwassmann-Wachmann 1, 218P/LINEAR, 221P/LINEAR, 318P/McNaught-Hartley, C/2010 FB87 (WISE-Garradd), C/2010 G2 (Hill), C/2011 KP36, C/2011 L4 (PANSTARRS) and C/2013 US10 (Catalina). Several of these objects have never been studied before. We analyzed images in V and R filters taken with the 2.15 m telescope at Complejo Astronómico El Leoncito (CASLEO), Argentina, to characterize their dust coma features and to investigate the morphology, photometry and dust production. The morphological analysis shown many differences among the sample of objects observed, showing several structures from the large twisted regions to collimated jets that do not follow the anti-solar direction. The Afρ values measured in a reference aperture of radius ρ = 10 4 k m shown a scenario of bodies ranging from dust poor to very active ones. This is confirmed by the quantitative estimate of the dust mass-loss rate obtained from the photometric data. Highlights: We studied the activity of a group of long and short period comets. The SP comets are 22P/Kopff, 29P/Schwassmann-Wachmann 1, 218P/LINEAR, 221P/LINEAR and 318P/McNaught-Hartley. The LP comets are C/2010 FB87 (WISE-Garradd), C/2010 G2 (Hill), C/2011 KP36, C/2011 L4 (PANSTARRS) and C/2013 US10 (Catalina). We analyzed images in V and R filters to investigate the morphology, photometry and dust production.